LINGUISTIC AND SOCIO-HUMANITARIAN ISSUES OF PERSONNEL TRAINING AND EDUCATION ORGANIZATION BASED ON DIGITAL TECHNOLOGIES AND INNOVATIVE APPROACH - Safarova Nargiza Bobomurodovna (Journals Park Publishing, 2024)
In this article, in accordance with the decision of the President of the Republic of Uzbekistan on measures to create conditions for the rapid introduction of artificial intelligence technologies, the rapid introduction of artificial intelligence technologies and the development of a highly qualified staffing system in this field Information about the capture is given. In the article, the importance of the developing digital technologies and innovative approach in making the educational process more qualitative and effective, the importance of the development of the educational system based on modern technologies, comments on the role of digital educational resources and their transfer to the educational process. The given article mainly shows digital technologies in the field of education and their importance in making the educational process more effective and interesting. Also, the importance of paying attention to these areas in the process of personnel training and education is shown.
Keywords: Educational system, field of education, technology, digital technologies, digital educational resources, educational system. digitization, technology, digital knowledge, information, internet, mobile network, computer, innovation, economy, education, knowledge, artificial intelligence, integration, electronic environment, interactive.